2018
DOI: 10.1038/s41598-018-31441-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma gelsolin promotes re-epithelialization

Abstract: Woundhealing disorders characterized by impaired or delayed re-epithelialization are a serious medical problem that is painful and difficult to treat. Gelsolin (GSN), a known actin modulator, supports epithelial cell regeneration and apoptosis. The aim of this study was to estimate the potential of recombinant gelsolin (rhu-pGSN) for ocular surface regeneration to establish a novel therapy for delayed or complicated wound healing. We analyzed the influence of gelsolin on cell proliferation and wound healing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…In the present study, we have demonstrated that rhuGSN (0.375-12.5 μg/mL) increases cell viability and promotes fibroblast proliferation, leading to wound healing in 3T3-L1 cells. Our findings are consistent with previous reports demonstrating the proliferative effect of recombinant pGSN on human corneal epithelial cells and mesangial cells [34][35][36]. The rhuGSN also exhibited antioxidant property by protecting the cells from oxidative stress induced by H 2 O 2 exposure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we have demonstrated that rhuGSN (0.375-12.5 μg/mL) increases cell viability and promotes fibroblast proliferation, leading to wound healing in 3T3-L1 cells. Our findings are consistent with previous reports demonstrating the proliferative effect of recombinant pGSN on human corneal epithelial cells and mesangial cells [34][35][36]. The rhuGSN also exhibited antioxidant property by protecting the cells from oxidative stress induced by H 2 O 2 exposure.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, gelsolin also exhibits anti-inflammatory properties, and its ability to modulate the polymeric state of actin is pivotal for cell proliferation and final topology of cell-cell layering [46]. In an ocular surface regeneration model, recombinant plasmatic gelsolin therapy promoted wound healing by acting on the epithelial cells as well as in deeper corneal layers such as the stroma, where fibroblasts are differentiated into myofibroblasts [34]. The role of gelsolin as actin regulatory protein is well established [15,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis and septic shock represent very serious medical conditions that require a complex therapeutic approach and use of a spectrum of drugs assuring multidirectional biological activity. A compelling number of studies report that pGSN, apart from having actin-scavenging properties, exerts a number of effects in pathogenesis including protection against infections, implication in wound healing and re-epithelization, bone remodeling, and the stabilization of intracellular calcium concentrations [5,22]. Importantly, in mice not expressing GSN, dysfunction in inflammatory reactions, including the delayed in vivo migration of neutrophils and impaired chemotaxis was observed [23].…”
Section: Discussionmentioning
confidence: 99%
“…patients with diabetes. Of note, treatment with gelsolin has been observed to decrease IL-6 levels in mice (Cheng et al, 2017) and has been suggested to promote epithelial repair (Wittmann et al, 2018) . The development of therapies to stabilise the gelsolin levels could hence be of direct therapeutic value for treating COVID-19.…”
Section: Tissue Injury and Dysregulation Of Modulators Of Inflammationmentioning
confidence: 99%
“…Of note, treatment with gelsolin has been observed to decrease IL-6 levels in mice (Cheng et al, 2017) . Gelsolin treatment has been suggested to promote epithelial repair (Wittmann et al, 2018) .…”
Section: Supplementary Informationmentioning
confidence: 99%